Jabal Ash-Sharah, Jordanien: Nabatäische Wohn- und Wirtschaftsstrukturen im Hinterland von Petra - Ladurner, Mechthild (e-Forschungsberichte des DAI, 2023)
The 2014 survey campaign in the hinterland of Petra constitutes a continuation of a new research project initiated in 2013 (eDAI-F 2014-2, 2014, 73– 77), focused on the study of Nabataean/Roman farmsteads and their paleoenvironment. Beyond the evaluation of previous fieldwork, a total of seven sites along the Jabal ash-Sharah where surveyed during this season documenting architecture, landscape/topography and surface-finds. So far, this data allows an insight into the typology of architecture, its position within the landscape, surrounding installation and its relation to the regional and supraregional road network. Furthermore, these sites serve as nuclei for a study of the spatial organization of the area.